Emergent quantum phenomena uncovered by extreme conditions and peculiar defects - Rabello, Aryella Faé (2025)
This thesis investigates quantum phenomena in correlated materials by studying their physical properties under extreme conditions, including low temperatures (T down to 1.5 K), high pressures (P up to 38 GPa), and magnetic fields (B up to 9 T). The resulting TPB phase diagrams provide a framework to understand the interactions between electronic, spin, and lattice degrees of freedom that determine the low-energy scales governing collective quantum behavior. In addition, this work examines disorder-driven interactions in quantum materials in order to clarify the role of atomic defects in many-body quantum systems. The main focus of this thesis is FeGa3, a narrow-gap intermetallic semiconductor that serves as a model system for studying the influence of atomic defects on correlated electronic states. By systematically comparing pristine FeGa3 with samples containing Fe antisite defects (Fe0.258Ga0.742), this study shows how structural defects modify the electronic and magnetic ground states. High-pressure synchrotron X-ray diffraction, electrical transport, and Mossbauer spectroscopy demonstrate that antisite disorder destabilizes the non-magnetic semiconducting state, leading to the formation of local magnetic moments, in-gap states, and a pressure-induced transition to a magnetically correlated phase. These results indicate that antisite defects play an active role in shaping the electronic and magnetic properties of the system. Beyond FeGa3, the thesis includes complementary investigations of other quantum materials presented in the appendices. In Fe0.05ZrTe2, low-temperature Mössbauer spectroscopy was used to probe a possible charge density wave (CDW) transition, illustrating the applicability of this technique to collective electronic phenomena. In a separate study, SnO was investigated under combined pressure and magnetic field, revealing the emergence of a second superconducting dome in the temperaturepressuremagnetic field phase diagram. This result underscores the relevance of electrical transport measurements performed under simultaneous extreme conditions in the LQMEC-IFUSP laboratory. Overall, this work contributes to the understanding of how pressure, disorder, and external fields influence correlated quantum materials. By clarifying the mechanisms governing the investigated systems, the results presented here provide a basis for exploring and controlling quantum states in materials where defects and external tuning parameters play a central role.